2022
DOI: 10.3390/buildings12122267
|View full text |Cite
|
Sign up to set email alerts
|

Computational Optimization of 3D-Printed Concrete Walls for Improved Building Thermal Performance

Abstract: Three-dimensional printing technologies are transforming various sectors with promising technological abilities and economic outcomes. For instance, 3D-printed concrete (3DPC) is revolutionizing the construction sector with a promise to cut projects’ costs and time. Therefore, 3DPC has been subjected to extensive research and development to optimize the mechanical and thermal performance of concrete walls produced by 3D printing. In this paper, we conduct a comparative investigation of the thermal performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The stagnant air acts as an insulator, impeding heat transfer via convective and radiative means. Because air movement is restricted, conduction becomes the primary mechanism for heat movement inside this region of the walls [19].…”
Section: Methodology and Analysismentioning
confidence: 99%
“…The stagnant air acts as an insulator, impeding heat transfer via convective and radiative means. Because air movement is restricted, conduction becomes the primary mechanism for heat movement inside this region of the walls [19].…”
Section: Methodology and Analysismentioning
confidence: 99%
“…In regard to 3DP concrete walls, it was observed that they exhibit superior thermal performance compared to conventional constructions. However, this performance is significantly influenced by factors such as the infill structure, concrete composition, and void fraction [67]. In a study by Briels et al [68], the use of internal cellular structure with encapsulated air-filled voids was investigated, revealing that lightweight concrete elements can achieve commendable thermal performance with lower resource consumption.…”
Section: Summary Of Total Materials Impactsmentioning
confidence: 99%
“…They found that SIP thickness is the dominant factor that affects its thermal performance, and the reduction in the R-value of the SIP caused by the embedded camlock systems is less than 13.8%. AlZahrani et al [2] performed optimization on concrete walls using 3D-printed technology. They found that the infill structure of the walls affects their thermal conductivities and, thus, their thermal performance.…”
Section: Energy Saving Through Building Envelopmentioning
confidence: 99%